An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. (1st March 2014) - Fernández-Aldea, A F; Barão, K R; Grazia, J; Ferrari, A
Abstract: "Integrative taxonomy" is a conceptual multisource approach in which the nomination of a species is considered as a hypothesis subject to evaluation through different empirical evidence. In this study, we followed a hypothesis-driven approach, where a set of specimens are used to test previous hypotheses about the existence of species. Thus, Oenopiella Bergroth is revised, based on morphology with emphasis on the genitalia of both sexes. Oenopiella unidentata Spinola, Oenopiella punctaria Stål, and Oenopiella pallidula Stål are redescribed and illustrated, and two new species are described, Oenopiella ventanensis Grazia sp. nov. from Argentina and Oenopiella flonensis Fernández-Aldea sp. nov. from southern Brazil. A key to separate the species is provided. The reliability of O. punctaria and O. unidentata is evaluated through a reanalysis of their morphological characters, by exploring differences in qualitative and quantitative morphologic characteristics. All lines of evidence support these species hypotheses.